Reserves and Resources Application in Welcoming Industry 4.0 Challenge - Reza Alfajri; Hanief Jauhari; Andar Parulian Hutasoit; Sakti Parsaulian Siregar; Ernita Sembiring Meliala (Testing Center for Oil and Gas LEMIGAS, 2020)
In the era of industry 4.0, digitalization is a very significant step to adopt in a company. Every worldly renowned industry, oil and gas included, needs to assimilate this term into its business process. Reserves and resources report depicts an oil and gas company future cash flow, wealth, performance, as well as growth. Therefore, creating and managing this report need meticulous attention. In order to comply with demand in industry 4.0 and simplify reserves and resources reporting process, reserves and resources database and web-based application need to be developed. First task to carry in establishing database is to create and input master data. Companies’ asset is classified into four common entities: asset, area, structure, and layer – as the smallest entity. Layer contains fluid type and oil and gas specific attributes. After master data is established, a web-based application to handle data transaction and reporting is developed. In order to maintain data security, access to this application is restricted into four roles: data entry user, data approval user, administrator, and management. Every role has its own privilege, for example data entry user can create, edit, and view data, while management can only view it. Other employees that need to access this application are based on management approval and restricted into view privilege under their asset location. This application has already been tested in two reserves and resources reporting window, and underwent bug-fixing and improvement process. Implementing this application in oil and gas company’s business process gives several benefits: minimizing human error, establishing a single data source, and cutting time consumption in creating reserves and resources report. This application is the solution in creating and managing the report, as well as displaying data in graphical view to help management makes corporate decision.